2002
DOI: 10.1183/09031936.02.02092001
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses to the 6-min walk test in patients with chronic obstructive pulmonary disease

Abstract: The 6-min walking test (6MWT) is frequently used to assess functional capacity in chronic cardiopulmonary disorders because of its simplicity. The study examines the physiological responses during encouraged 6MWT in patients with chronic obstructive pulmonary disease.Pulmonary oxygen (O 2 ) uptake (V9O 2 ) was measured in 20 male patients (age 66¡6 yrs, forced expiratory volume in one second 45¡14% predicted) during 6MWT and incremental cycling, in random order. O 2 tension in arterial blood, carbon dioxide te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
175
1
16

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(210 citation statements)
references
References 25 publications
18
175
1
16
Order By: Relevance
“…This is probably due to the differences between these two exercise modalities. In comparison with cycling, walking has been shown to be less fatiguing and to produce less lactate at similar V9O 2 levels [19][20][21]. Hence, patients are able to exercise for longer periods.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably due to the differences between these two exercise modalities. In comparison with cycling, walking has been shown to be less fatiguing and to produce less lactate at similar V9O 2 levels [19][20][21]. Hence, patients are able to exercise for longer periods.…”
Section: Discussionmentioning
confidence: 99%
“…However, incremental tests are not the only way of determining maximal responses to exercise among patients with chronic lung disease. In this context, Troosters et al 34 demonstrated that the VO 2 peak and HR expressed as percentage of the predicted value (82%±9% and 85%±9%, respectively) was similar between the 6-MWT (1.40±0.29 L/min) and the maximum incremental test on a cycle ergometer (1.41±0.18 L/min) 34 . Casas et al 35 corroborated these findings by demonstrating that patients with COPD achieved 90% of the VO 2 observed in a maximal test on a cycle ergometer from the third minute of the 6-MWT.…”
Section: Discussionmentioning
confidence: 99%
“…It is also suitable for individuals who use orthopedic devices to walk, people with difficulties associated with maintenance of balance 22 and even for patients with severe chronic obstructive pulmonary disease. For these patients, the 6MWT can be regarded as a "near maximal" test because energy expenditure during the test comes close to the maximum, according to individual symptoms 23,24 .…”
Section: Discussionmentioning
confidence: 99%